2020
DOI: 10.3390/medicina56030102
|View full text |Cite
|
Sign up to set email alerts
|

An Upfront Two-Stent Strategy for True Coronary Bifurcation Lesions with A Large Side Branch in Acute Coronary Syndrome: A Two-Year Follow-Up Study

Abstract: Background and Objectives: Little is known about the upfront two-stent strategy (U2SS) for true coronary bifurcation lesions (CBLs) in acute coronary syndrome (ACS). We aimed to present our two-year follow-up results on the U2SS by using different two-stent techniques for the true CBL with a large side branch (SB) in ACS patients, including unstable angina (UA), non-ST-segment elevation myocardial infarction (NSTEMI), and ST-segment elevation myocardial infarction (STEMI), and to identify independent predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
3
2
0
Order By: Relevance
“…The achievement of post procedure TIMI grade 3 flow in all patients suggests the absence of any ischemic myocardial areas. A similar finding was reported by Yurtdas et al [4].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The achievement of post procedure TIMI grade 3 flow in all patients suggests the absence of any ischemic myocardial areas. A similar finding was reported by Yurtdas et al [4].…”
Section: Discussionsupporting
confidence: 91%
“…The mean age of patients (65.3 ± 11.1 years) undergoing PCIs in this study falls within the confidence limits reported by other studies (58 ± 11 years to 71 ± 10 years; Table 5). The percentages of comorbidities, such as hypertension, DM, and smoking, reported in this study are also comparable to those in previous studies [4] [19]- [38]. Additionally, the percentages of patients presenting with CSA, UA, and ACS are similar to those of previous findings [15] [19] [41].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We have higher percentage of kissing balloon inflation, more fluoroscopy time and contrast volumes in patients managed with two stents and this is consistent with the results of Salina et al [16], Dudek et al [18], Choi et al [19], Kwan et al [20] and Yurtdas et al [21]. In the present study, crush techniques and T stenting were the most utilized stenting techniques in patients managed with two stents and these findings are in line with Choi et al [19], Kwan et al [20] and Yurtdas et al [21].…”
Section: Discussionsupporting
confidence: 91%